Diseminasi Pembuatan Cabai Bubuk dan Pengemasannya untuk Peningkatan Nilai Tambah Usaha Ibu PKK Desa Tanjung Baru: Dissemination of Chili Powder Production and Packaging to Increase the Added Value of PKK Women's Businesses in Tanjung Baru Village - Defira, Citra; Prayitno, Citra Pratiwi; Ichsan, Onne Akbar Nur; Antonio, Jerry; Robbani, Syifa’ (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Tanjung Baru Village is one of the major chili-producing areas in Ogan Ilir Regency, where high daily production often leads to substantial losses due to sharp price fluctuations during peak harvest periods. This issue is exacerbated by the community's limited knowledge of postharvest and processing technologies, leading to a heavy reliance on the sale of fresh chilies with short shelf lives. This community service program aims to enhance local capacity—particularly among women's groups (PKK)—by disseminating appropriate technology for processing chilies into chili powder as a value-added product. The program consisted of lectures, equipment demonstrations, hands-on practice, and evaluation through pre-test and post-test assessments. The results indicate that participants were highly engaged and completed all processing stages, including sorting, drying with a food dehydrator, grinding, sieving, and packaging. Although the increase in average knowledge score from 72.67 to 76 was not substantial, observational assessments showed a pronounced improvement in participants' psychomotor skills, reflected in their ability to produce chili powder with acceptable sensory quality. Overall, the dissemination activity effectively strengthened the community's technical competencies and holds strong potential to support the development of small-scale chili powder enterprises as a strategy to improve product value, reduce postharvest losses, and enhance local economic resilience.